2017
DOI: 10.1017/s0033583517000075
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme's lectin-like characteristics facilitates its immune defense function

Abstract: Abstract. Interactions between human lysozyme (HL) and the lipopolysaccharide (LPS) of Klebsiella pneumoniae O1, a causative agent of lung infection, were identified by surface plasmon resonance. To characterize the molecular mechanism of this interaction, HL binding to synthetic disaccharides and tetrasaccharides representing one and two repeating units, respectively, of the O-chain of this LPS were studied. pH-dependent structural rearrangements of HL after interaction with the disaccharide were observed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
0
44
0
2
Order By: Relevance
“…The encoding protein of these genes include (Figure 3B, Dataset S4): (i) C‐type lectins (such as CLEC‐10, CLEC‐40, and CLEC‐170), a family of surface receptors known to recognize microbial carbohydrate moieties, which can sense products from dying cells and transduce inflammatory signals that modulate the immune system 51 ; (ii) F‐box A protein (FBXA‐20, FBXA‐59, FBXA‐60, FBXA‐82, and FBXA‐156), one family proteins with F‐box motif that involves in ubiquitin‐mediated proteolysis, which function as the key regulator in many pathways of cell signalling, transcription, and cell division 52 ; (iii) Lysozymes. In C. elegans , there are ten genes encoding lysozymes for antimicrobial proteins against bacteria 53 . Our results showed that most of lysozymes in C. elegans were induced at different time point post infection, and LYS‐2 and LYS‐3 were consistently induced throughout the infection process (Figure 3B, Dataset S4).…”
Section: Resultsmentioning
confidence: 72%
“…The encoding protein of these genes include (Figure 3B, Dataset S4): (i) C‐type lectins (such as CLEC‐10, CLEC‐40, and CLEC‐170), a family of surface receptors known to recognize microbial carbohydrate moieties, which can sense products from dying cells and transduce inflammatory signals that modulate the immune system 51 ; (ii) F‐box A protein (FBXA‐20, FBXA‐59, FBXA‐60, FBXA‐82, and FBXA‐156), one family proteins with F‐box motif that involves in ubiquitin‐mediated proteolysis, which function as the key regulator in many pathways of cell signalling, transcription, and cell division 52 ; (iii) Lysozymes. In C. elegans , there are ten genes encoding lysozymes for antimicrobial proteins against bacteria 53 . Our results showed that most of lysozymes in C. elegans were induced at different time point post infection, and LYS‐2 and LYS‐3 were consistently induced throughout the infection process (Figure 3B, Dataset S4).…”
Section: Resultsmentioning
confidence: 72%
“…The relation between pH values and lysozyme (HL and HEWL) structures is indicated by the overlay presentations shown in Figure 8c,d. When human lysozyme is encapsulated in nanoparticles for a therapeutic use, precise knowledge of the submolecular details about its carbohydrate affinity 14 is of importance because this part of the molecule can be considered as a vital target unit. Three essential amino acids—Tyr63 (yellow), Arg98 (red), and Trp109 (blue)—are stabilizing the complex (5lsh.pdb), highlighted in Figure 8e.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Overlay of two human lysozyme (HL) structures for a comparison of pH-dependent effects. (e) Backbone and (f) surface representation of human lysozyme in complex with the tetrasaccharide O-antigen LPS fragment from K. pneumoniae (5lsh.pdb 14 ). Crucial amino acids that are stabilizing the complex are highlighted on the left side by the following color code: Tyr63 (yellow), Arg98 (red), and Trp109 (blue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some insights on molecular basics of LPS binding by LZ were recently provided by Zhang et al. who used precise methodology (NMR spectroscopy, molecular modeling, and X-ray crystallography) to study interactions between human LZ and synthetic oligosaccharides representing repeating unit(s) of K. pneumoniae O1 O-PS [ 26 ]. The LZ molecules underwent structural rearrangements after the interaction with synthetic oligosaccharides.…”
mentioning
confidence: 99%